Technical bases of biliary tract surgery - Medeiros, Aldo Cunha; Araújo-Filho, Irami; Dantas-Filho, Antônio Medeiros (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2023)
ABSTRACT Gallstone disease and complications from gallstones are a common clinical problem. The clinical presentation is from asymptomatic and attacks of biliary pain requiring elective or emergency surgery. Bile duct stones are associated with cholelithiasis. The total cholecystectomies are the most common surtery performed for cholelithiasis, the presence of bile duct stones is 10%, but a small percentage of these will develop common bile duct stones. In order to avoid complications of choledocholithiasis, these stones should be removed. The direct open surgical approach to the bile duct can be done, but with the advent of advanced endoscopic, radiologic, and laparoscopic surgical techniques have increased in number. In the era of laparoscopy and mini-invasiveness, therapeutic approaches can be performed in two sessions or in one session. Comparison of these two approaches showed equivalent success rates, but the one-session treatment is characterized by a shorter hospital stay, and more cost benefits. The aim of this review article is to provide the medical students readers with a general summary of gallbladder stone disease in association with the presence of common bile duct stones by discussing surgical anatomy, clinical and diagnostic aspects, and the possible treatments.